Impression Management: Henry Cavill on Superman Actor Change on Instagram @Henrycavill - Ariabagas Prabangkara Athallariq; Prima Mulyasari Agustini (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2025)
The modern entertainment industry is a significant business. The mass media currently focuses on popularizing and idolizing celebrities in the entertainment field. Public Relations practitioners who work as publicists play a crucial role in this industry. Gaining positive publicity or reframing negative publicity from issues and controversies can attract more attention at a significantly lower cost than purchasing publicity through advertising. Henry Cavill is a well-known actor and celebrity who consistently ranks as one of Hollywood's most prominent actors. Recently, he received news that he would not return to portray Superman after announcing his departure from The Witcher. Following the announcement that the DCEU was letting go of Henry Cavill, rumors appeared regarding the reasons for his potential dismissal. This situation is where Henry Cavill should engage a professional Public Relations agency. This research explores Henry Cavill's Impression Management strategies in this situation. The research method employed is a qualitative approach. The subject of the study is Henry Cavill's Impression Management regarding the actor's change for Superman on his Instagram account @henrycavill—data collected through text analysis and literature review. Henry Cavill could enlist a professional Public Relations agency to dispel rumors about his departure from The Witcher and counter the allegations that he is a poor worker. With the assistance of a professional Public Relations agency, the situation could improve significantly.